KEMAMPUAN KONEKSI MATEMATIS DALAM PEMECAHAN MATEMATIKA DITINJAU DARI ADVERSITY QUOTIENT DAN GENDER - Sukmaningrum, Ratna; Afifah, Dian Septi Nur; Purnawananti, Yepi Sedya (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2026)
This study aims to describe students' mathematical connection abilities in solving mathematical problems in terms of Adversity Quotient (AQ) levels and gender. Mathematical connection ability is a crucial competency in mathematics learning that enables students to relate mathematical concepts, as well as connect mathematics to other disciplines and real-life situations. Adversity Quotient, categorized into climbers, campers, and quitters, reflects students' persistence in facing challenges, while gender influences students' approaches to problem-solving. This research employs a descriptive qualitative approach involving eighth-grade students at SMP Negeri 1 Pakel. Data were collected through mathematical problem-solving tests and in-depth interviews. The findings indicate that students with high AQ (climbers), both male and collected through mathematical problem-solving tests and in-depth interviews. The findings indicate that students with high AQ (climbers), both male and female, demonstrate a more comprehensive conceptual understanding and stronger mathematical connection abilities compared to campers and quitters. Additionally, differences in problem-solving approaches were observed between male and female students. These results have important implications for educators in designing instructional strategies that take into account AQ and gender to effectively enhance students' mathematical connection skills.